PERENCANAAN PEMBANGUNAN DESA DI DESA NANGA UNGAI KECAMATAN KAYAN HULU KABUPATEN SINTANG - Susi Krisjuyani (Universitas Kapuas Sintang, 2025)
Village development is the key to creating equitable welfare, reducing poverty, and supporting sustainable development. Well-planned, participatory, and sustainable village development is the key to creating a more just, prosperous, and competitive development. Village development planning is a critical first step to achieving effective and sustainable development goals. In Nanga Ungai Village, Village Development Planning has not been carried out optimally by the Village government, it occurs due to the lack of community participation in planning, the lack of capacity of the village government in preparing plans, budget limitations, and unclear development priorities. Based on these problems, the author is interested in answering these problems by trying to answer the formulation of the problem: How is Village Development Planning in Nanga Ungai Village, Kayan Hulu District, Sintang Regency? The purpose of this research is to make a description, description or painting systematically, factually, and accurately about the facts or phenomena being investigated. Then the method used, namely qualitative descriptive research method. The object of this research is Village Development Planning in Nanga Ungai Village, Kayan Hulu District, Sintang Regency. The informants of this study were 4 people, as the consideration that those selected met the criteria according to the research objectives. The results showed that Village Development Planning in Nanga Ungai Village was quite good, carried out in advance deliberations, mapping problems and objectives of activities, determining activity implementers, preparing work plans, and socializing activities. Village development is funded by the Village Budget. Participants in the Village Deliberation, namely the village government, Village Consultative Body, Village Community Institutions, and elements of the village community, are funded by the APBDes.